Association of Plasmodium berghei With the Apical Domain of Hepatocytes Is Necessary for the Parasite's Liver Stage Development - Balasubramanian, Lakshmi; Zuzarte-Luís, Vanessa; Syed, Tabish; Mullick, Debakshi; Deb, Saptarathi; Ranga-Prasad, Harish; Meissner, Jana; Almeida, Ana; Furstenhaupt, Tobias; Siddiqi, Kaleem; Prudêncio, Miguel; Rodrigues, Cecilia M. P.; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Plasmodium parasites undergo a dramatic transformation during the liver stage of their life cycle, amplifying over 10,000-fold inside infected hepatocytes within a few days. Such a rapid growth requires large-scale interactions with, and manipulations of, host cell functions. Whereas hepatocyte polarity is well known to be critical for liver function, little is presently known about its involvement during the liver stage of Plasmodium development. Apical domains of hepatocytes are critical components of their polarity machinery and constitute the bile canalicular network, which is central to liver function. Here, we employed high resolution 3-D imaging and advanced image analysis of Plasmodium-infected liver tissues to show that the parasite associates preferentially with the apical domain of hepatocytes and induces alterations in the organization of these regions, resulting in localized changes in the bile canalicular architecture in the liver tissue. Pharmacological perturbation of the bile canalicular network by modulation of AMPK activity reduces the parasite’s association with bile canaliculi and arrests the parasite development. Our findings using Plasmodium -infected liver tissues reveal a host-Plasmodium interaction at the level of liver tissue organization. We demonstrate for the first time a role for bile canaliculi, a central component of the hepatocyte polarity machinery, during the liver stage of Plasmodium development.